Arrhythmias in adult patients with congenital heart disease and pulmonary arterial hypertension. Issue 23 (18th May 2018) - Drakopoulou, Maria; Nashat, Heba; Kempny, Aleksander; Alonso-Gonzalez, Rafael; Swan, Lorna; Wort, Stephen J; Price, Laura C; McCabe, Colm; Wong, Tom; Gatzoulis, Michael A; Ernst, Sabine; Dimopoulos, Konstantinos
Abstract : Objectives: Approximately 5%–10% of adults with congenital heart disease (CHD) develop pulmonary arterial hypertension (PAH), which affects life expectancy and quality of life. Arrhythmias are common among these patients, but their incidence and impact on outcome remains uncertain. Methods: All adult patients with PAH associated with CHD (PAH-CHD) seen in a tertiary centre between 2007 and 2015 were followed for new-onset atrial or ventricular arrhythmia. Clinical variables associated with arrhythmia and their relation to mortality were assessed using Cox analysis. Results: A total of 310 patients (mean age 34.9±12.3 years, 36.8% male) were enrolled. The majority had Eisenmenger syndrome (58.4%), 15.2% had a prior defect repair and a third had Down syndrome. At baseline, 14.2% had a prior history of arrhythmia, mostly supraventricular arrhythmia (86.4%). During a median follow-up of 6.1 years, 64 patients developed at least one new arrhythmic episode (incidence 3.47% per year), mostly supraventricular tachycardia or atrial fibrillation (78.1% of patients). Arrhythmia was associated with symptoms in 75.0% of cases. The type of PAH-CHD, markers of disease severity and prior arrhythmia were associated with arrhythmia during follow-up. Arrhythmia was a strong predictor of death, even after adjusting for demographic and clinical variables (HR 3.41, 95% CI 2.10 to 5.53, p<0.0001). Conclusions: Arrhythmia is common in PAH-CHD and is associated with an adverse long-term outcome, even when managed in a specialist centre.